English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-09-27 03:54:35 · 22 answers · asked by nitish _4u 1 in Science & Mathematics Mathematics

22 answers

0=0.
1*0=2*0
1*0/0=2*0/0
0/0=1
1*1=2*1
1=2

Of course, 0/0=1 is false, but that's the step needed to prove what you ask.

2006-09-27 04:17:06 · answer #1 · answered by zex20913 5 · 0 2

If Red = Blue
and False = True
then 1= 2

2006-09-27 04:17:03 · answer #2 · answered by davidosterberg1 6 · 1 0

A funny way!!!
1/0 = infinity----(1)
2/0 = infinity-----(2)
Equating (1) and (2)
1/0=2/0
Hence 1 = 2

2006-09-27 05:25:16 · answer #3 · answered by Anonymous · 0 0

1=2 in Mars. Now you prove it wrong!

2006-09-27 03:58:31 · answer #4 · answered by Anonymous · 1 1

This is one way of doing it, cool right?

let a = b

a² = ab
Multiply both sides by a
a² + a² - 2ab = ab + a² - 2ab
Add (a² - 2ab) to both sides
2(a² - ab) = a² - ab
Factor the left, and collect like terms on the right
2 = 1
Divide both sides by (a² - ab)

2006-09-27 04:36:54 · answer #5 · answered by Anonymous · 0 1

Yes I can. :)

Follow along:
1. Let a = b

2. a^2 = ab (multiply both sides by a)

3. a^2 +a^2 = a^2 +ab (add a^2 to both sides)

4. 2a^2 = a^2 +ab (a^2 + a^2 = 2a^2)

5. 2a^2 - 2ab = a^2 +ab -2ab (subtract 2ab from both sides)

6. 2a^2 - 2ab = a^2 -ab (ab - 2ab = -ab)

7. 2(a^2-ab) = 1(a^2-ab) (factoring out a common term)

8. 2 = 1 (cancel out the a^2-ab on both sides)

So therefore, 2=1

:)

2006-09-27 04:02:28 · answer #6 · answered by SmileyGirl 4 · 0 1

let a=b
multiplying a both side
aa=ab
subtracting by bb
aa-bb=ab-bb
(a+b)(a-b)=b(a-b)
(a+b)=b
b+b=b as a=b
2b =b
2=1
1=2
hence proved

2006-09-27 04:24:54 · answer #7 · answered by Nitin Pal 2 · 0 1

1+1=2-1 (add 1 on LHS and subtract 1 on RHS)
then, cancel out 1 on both sides and..........its proved

2006-09-27 03:59:16 · answer #8 · answered by mr crazy 2 · 1 2

let a=b------------'1'

multiply both sides by a
then a*a=ab

subtract b*b from both sides
then a*a-b*b=ab-b*b

=>(a-b)(a+b)=b(a-b)
cancel (a-b) on both sides

=>(a-b)=b
=>a=b+b
=>a=2b

from '1' =>a=2a

cancel a on both sides
then we get 1=2

2006-09-27 19:31:54 · answer #9 · answered by praveen 1 · 0 0

Not correctly!

But there are many "proofs" that make claims like that, which involve math errors like division by zero subtly hidden inside.

2006-09-27 03:57:46 · answer #10 · answered by poorcocoboiboi 6 · 2 0

fedest.com, questions and answers